Das rezeptionsgrammatische Modell am Beispiel der erweiterten Substantivphrase in ausgewählten deutschen Wirtschaftstexten - Ditlevsen, Marianne (HERMES - Journal of Language and Communication in Business, 1999)
It is a well-known fact that many students of German have difficulties reading and thereby understanding LSP texts written in German. Why? This is the kind of question that is normally answered within a cognitive framework. In this article, however, the point of departure will be syntactic. The perspective will be receptive (and not productive or neutral as is the case with traditional German grammar and generative grammar, respectively). The signals on the text surface will be given high priority due to the receptive perspective. The main purpose of the article will be to present and discuss a syntactic model for analysing German NPs in economic texts from a receptive perspective. The model is based on four description principles: the “Phrase”, the “Rahmen”, the ”Feld” and finally the “Ketten” principles. The “Ketten” principle is the most characteristic for the NP model presented here as it offers an alternative way of looking at post-modifiers. In the article it will then be argued that the model is useful for description and that the results allow us to make hypotheses as to answering the question above.